Identification of distortion of the navigator's time in model experiment - Nosov, P.S.; Cherniavskyi, V.V.; Zinchenko, S.M.; Popovych, I.S.; Prokopchuk, Y.A.; Safonov, M.S. (KU Publ., 2020)
This article discusses a formal analysis of time perception made by sea transport navigators being in critical situations while performing vessel navigation. The carried out analysis of experimental data and investigations of marine accidents provided us with valuable insights of having wide range of cases in which navigators, while performing complex maneuvers (i.e. mooring operation), are highly likely to be involved into facing challenges of getting poor time comprehension during template implementation process. It is worth mentioning that while having it this very issue is being influenced on by external and internal factors. It, for its part, is noticed to considerably contribute into the increased likelihood of accidents. The main goal of this study is reported to be the development of a concept of having formal and automated means and methods for the identification distortion of the navigator's time (DNT) as being an indicator of negative manifestation of human factor in critical situations. For the sake of having been able to accomplish this goal a generalized model for the formation of t DNT was proposed as well as mathematical models and automated tools were introduced to be used for DNT intervals identification when analyzing the physical trajectory of the vessel's movement. Besides, the generating individual time codes in emergency situations system is managed to be successfully revealed. Moreover, the carried out experiments using the certified navigation simulator Navi Trainer 5000 are said to have confirmed the convincing cogency and to have made clear evidences of providing practical value of the proposed approaches. It goes without saying that these issues are sure to significantly improve the safety-driven process of keeping a navigational watch while navigating a vessel.
Модельдік тəжірибеде навигатор уақытының бұрмалануын анықтау
Идентификация дисторсии времени навигатора в модельном эксперименте
Keywords: experimental data; navigator's time distortion; ergatic and automated systems